PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KOPI KENANGAN MANADO - intan, avrily (JURNAL ADMINISTRASI BISNIS, 2025)
Human resources are an essential factor in achieving organisational success, with employee performance playing a crucial role. Two main factors that influence performance are organisational culture and work environment. Organisational culture refers to shared values, beliefs, and norms that shape employee behaviour and attitudes, while the work environment includes physical and non-physical aspects that affect productivity. This study aims to determine the influence of organisational culture and work environment on employee performance at Kopi Kenangan Manado. The research involved 36 employees selected through purposive sampling. Data were analysed using multiple regression analysis, including F-test, t-test, R-square determination, and multiple correlation tests. The results showed that (1) simultaneously, organisational culture and work environment significantly affect employee performance, (2) organisational culture positively influences employee performance, and (3) the work environment also has a positive effect. These findings suggest that both factors are interconnected and essential in enhancing performance. Therefore, Kopi Kenangan Manado is encouraged to strengthen organisational culture by integrating values of openness, honesty, and responsibility, as well as providing a supportive work environment that fosters collaboration and rewards achievement. This will improve employee morale, ownership, and overall performance.